The Impact of Higher Secondary Level Entrance Examination Score on Academic Performance in the First Year of Engineering: A case Study - Mourya, Archana; Unhale, Rupali; Aher, Mohini; Bharambe, Leena; Kshirsagar, Monali; Patil, Rohini; Bhalerao, Anuradha; Nandurkar, Keshav (Journal of Engineering Education Transformations, 2026)
The transition from higher secondary education to undergraduate engineering programs in India is frequently shaped by standardized entrance examinations such as the Joint Entrance Examination (JEE), and State Common Entrance Test (CET). This research paper presents a case study exploring the relationship between entrance examination performance and the academic performance of First-Year Bachelor of Technology students, assessed through their cumulative grade point average (CGPA). The study interprets data from students admitted through entrance examinations over three academic years 2022– 23, 2023–24, and 2024–25.Utilizing statistical tools including correlation analysis, regression models, and Hypothesis test for mean differences. The analysis showed that the academic performance of high merit students is satisfactory, and the academic performance of low merit students goes on decreasing year-wise. The study also examines whether entrance exam scores can reliably predict students’ academic outcomes in their foundational year. The findings indicate a weak to moderate positive correlation between entrance examination scores and academic performance, as measured by CGPA. The relationship between students’ entrance scores and academic performance was examined by gender, as well as by the type of secondary school board attended, and the conclusions are discussed in this paper.